A Study on Front Desk Employees in India - Indu Misra, Lalat; Samal, Ansuman; B Pradhan, Bibhuti (International Journal of Psychosocial Rehabilitation, 2025)
The hospitality business is one of the most settled sub-adventures in the movement business, yet despite the modernization what's progressively, specific headway of this sub-industry, essential resource remains the human resource. In the settlement business the front office fills in as the first and one of the most noteworthy motivations behind contact with the guest. This examination bases on front office agents in regulatory and non-authoritative situations at various hotels in India and sees how delegates' statistics establishment, skills what's more, acknowledgment about the probability for future headway are related to their objectives to remain in this industry. The assessment was driven among 120 front desk region delegates and 40 front desk zone executives at hotels in India between 2012 and 2013. Most of the laborers were young, single and female. The results show that among those in non-authoritative positions 65 percent need to leave the business, while among bosses only 35 percent need to leave the business. In addition, the revelations show that working at a chain cabin and working as a boss improve the likelihood of surveying chances of headway as extraordinary. These results may bolster hotel boss understand the outlooks of their laborers and venture toward improving their motivation additionally, desk recognitions that will impact their status to remain in the hotel business